How important is compassionate healthcare to you? A comparison of the perceptions of people in the United States and Ireland. (March 2017) - Lown, Beth A; Dunne, Hilary; Muncer, Steven J; Chadwick, Raymond
Compassionate care requires understanding of another's pain or suffering, with commitment to doing something to relieve this. It is endorsed by nursing and other healthcare professionals in their codes of ethics as one of their main responsibilities. Yet too often it comes to public attention as a deficiency in healthcare organisations. Any effort to achieve meaningful quality improvement must start with a method of measuring patient experience. The Schwartz Center Compassionate Care Scale™ (SCCCS) is a unidimensional 12-item questionnaire with high internal reliability, developed from a study of physicians and recently hospitalised patients in the US. The present study extends usage of the SCCCS to a sample of the people in Ireland. The SCCCS again shows high internal reliability, with all items loading on a single factor. The findings indicate that recently hospitalised patients and non-hospitalised individuals were in agreement about the importance of the elements of compassionate care. Patients' ratings of their doctors' compassionate behaviours were significantly correlated with ratings of their healthcare team. However, patients reported that demonstration of compassion – whether by their doctor or the whole healthcare team – fell short of what they considered important. The SCCCS is a reliable and valid measure of perceptions of compassionate care across different countries, with potential to contribute to quality improvement in healthcare.